The transformation of traditional Malay male attire into contemporary casual wear / Muhammad Khalik Mustafa - Mustafa, Muhammad Khalik (2013)
This study is conducted to determine feedbacks upon the upgrading on the traditional Malay male attire’s design, which has been contemporize/ modernized, based on the character and the philosophy of the traditional Malay male attire. The wearing of traditional Malay male attire can be seen nowadays only in certain events and occasions. Among the attire studied here are baju kurung teluk belanga, baju sikap, baju kehormatan Barat, baju takwa, and baju kurung cekak musang. These original designs are given a new twist or in other word, transformation to adapt with the new fashion trends. Data was collected through: observation, evolution and questionnaire. The process making through idea sketches and prototype-making and actual product making are done based on results of these study. It can be concluded that modernization done on these traditional attire to be as casual wear for Malaysian men is acceptable.